2007
DOI: 10.1111/j.1442-2050.2007.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiation for patients with squamous cell carcinoma of the cervical esophagus

Abstract: Little is known concerning the role of concurrent chemoradiation (CCRT) in the management of carcinoma of the cervical esophagus. We retrospectively evaluated our treatment approach for patients with cervical esophageal cancer with special emphasis on CCRT with or without surgery. Medical records of 21 consecutive patients with cervical esophageal carcinoma treated mainly with CCRT (1997-2004) were reviewed, and factors that influenced patient survival were analyzed retrospectively. Nineteen received CCRT with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 14 publications
4
36
1
Order By: Relevance
“…These series were heterogeneous in terms of RT techniques, CHT regimens, and radiation doses. Approximately 59% of patients within these reports [6, 13, 15, 19, 2628] received RT alone, and 41% received CRT [7, 13, 14, 16, 19, 2629]. When a concurrent treatment approach was chosen, 22% of these patients received ICHT [16, 20, 29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These series were heterogeneous in terms of RT techniques, CHT regimens, and radiation doses. Approximately 59% of patients within these reports [6, 13, 15, 19, 2628] received RT alone, and 41% received CRT [7, 13, 14, 16, 19, 2629]. When a concurrent treatment approach was chosen, 22% of these patients received ICHT [16, 20, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Boost HDR 2x433%/2years; 19%/3years40NANOBurmeister et al; 2000 [12]34between cricoid and upper thoracic inlet. Extension allowedRCTNO50.4-65/NA88%125NANOYamada et al; 2006 [15]27NARCT (23)NO44-73.7/1.8-252%150Performance Status/Tumor lenghtNOWang et al; 2006 [18]35tumor located above the carinaRCTVarious: platinum-based + 5-FU/paclitaxel/etoposide24.5-64.8/1.847.7%/5yearsNANADose (>50Gy)NOUno et al; 2007 [14]21cricopharyngeal muscle to thoracic inletRCTNO40/2; Boost 20-34/NA52%9NAT-Stage, initial LC5/21Huang et al; 2008 [13]71 (50 curative intent)NARCTNO54/2.7 or 50-56/2 + Boost 14-20/237%/47% (curative group)/2years24/71NAGender, Age (>64)NOChou et al; 2010 [42]29 (14 RT)NARCTNO65 (60-75)/1.8-2NANANANA15/29Ma et al; 2011 [43]33 (69 upper thoracic esophagus)NARCTNO50.4 + Boost 9 or 59.4/each 1.8 (41.4), then 2x1.5 (18)80%/86%/3years6128NATong et al; 2011 [7]107 (21 RT)NARCTNO40-46 or 60-68/2NA8NANA68/107Cao et al; 2015 [28]115NART (80)/RCT (35)NO59.4-76/1.8-2.1283%/2years282Dose (>66 Gy)10/115Gikka et al; 2013, [20]55cricopharyngeus muscle to thoracic inlet (ca. 15 - 18 cm from the incisors)RCT…”
Section: Discussionmentioning
confidence: 99%
“…10,11 CDDP and 5-FU have been the standard chemotherapeutic agents in combination with radiotherapy for unresectable locally advanced thoracic esophageal cancer. 25,26 As for CRT regimens containing DOC, Font et al reported weekly DOC in combination with 66 Gy of radiation for unresectable thoracic esophageal cancer, and MST, 1-year OS, and 3-year OS were 5 months, 22%, and 0%, respectively. [20][21][22][23][24] Major toxicities were leukopenia, anemia, thrombocytopenia, esophagitis, and fistula formation.…”
Section: Discussionmentioning
confidence: 99%
“…For most patients with cervical esophageal cancer, radical surgery has mandated simultaneous total laryngectomy. Therefore, most patients with cervical esophageal cancer prefer CCRT to surgery due to the potential for laryngeal preservation [8]. In reality, however, not a few patients have experience a residual or recurrent tumor after CCRT.…”
Section: Discussionmentioning
confidence: 99%